“Who Gave Your Body Back to You?” Literary and Visual Cartographies of Erotic Sovereignty in the Poetry of Qwo-Li Driskill - Minai, Naveen (Imaginations)

(untitled) (York University, 2019)
US settler colonialism deploys metapolitical force against Indigenous epistemologies of land and body to destroy, erase, and contain Indigenous sovereignty and nationhood. Literary and visual grammars are crucial to these settler biopolitical and necropolitical technologies -- and Indigenous resistance. “Love Poems: 1838–1839” by Cherokee Two-Spirit poet scholar Qwo-Li Driskill challenges a settler-colonial cartography of time and space by disrupting the visual grammars of settler colonialism as they manifest in literary forms and rules. Driskill resists and refuses how settlers use writing as a visual and literary activity both to produce and reproduce time as linear and land as fungible object. Creating a specifically Indigenous literary/visual cartography of a Sovereign Erotic, I argue that Driskill disrupts settler heteronormativity of writing/mapping land and body, by impressing an Indigenous literary and visual form onto the page. These cartographies rewrite/map time and space according to Indigenous knowledges and practices of land and love. “Love Poems 1838–1839” is, then, a poem which is both story and map of erotic sovereignty as a crucial component of Indigenous nationhood and presence on the lands of the Americas.